PENGARUH LAMA PERENDAMAN EKSTRAK KULIT BATANG “KAJU BA’I” (Aglaia tomentosa) TERHADAP EFEKTIVITAS INSEKTISIDA NABATI PADA HAMA GUDANG KACANG HIJAU Callosobruschus sp (COLEOPTERA : BRUCHIDAE) - Mardiah Sarah; Sri Wahyuni; Willybrordus Lanamana (AGRICA, 2010)
This study aims to the influence of soaking bark extract “Kaju Ba’i” (Aglaia tomentose) and its effectiveness as a botanical insecticide of the green beans warehouse pest Callosobruschus app. The experiment was conducted at the Laboratory in the Faculty of Agriculture University of Flores, Ende, from September to October 2010. The research used a completely randomized design with 5 treatments of K0 (control), K1 (bark extract Kaju Ba’i immersed for one day), K2 (bark extract Kaju Ba’i immersed for two days), K3 (bark extract Kaju Ba’i immersed three two days), K4 (bark extract Kaju Ba’i immersed for four days) each treatment was repeated 10 times. Observed variables included mortality, contact nerve toxins and anti-oviposition activity. The results showed that the treatment K4 possesses the highest level of effectiveness, and cause mortality as contact poison (99%), nerve toxins (2.7%) and anti-oviposition (75%).